PENGARUH TRITERPEN TOTAL PEGAGAN (Centella asiatica (L) Urban) TERHADAP FUNGSI KOGNITIF BELAJAR DAN MENGINGAT PADA MENCIT JANTAN ALBINO (Mus musculus) YANG DIHAMBAT DENGAN SKOPOLAMIN - Herlina Herlina (Molekul, 2010)
Pegagan (Centella asiatica (L) Urban) has been described to posses CNS effects such as improving cognitive function, learning and memory. The aim of the research was to evaluate the effects of total triterpen’s pegagan extract on cognitive functions as the learning and memory performance in male albino mice (Mus musculus) inhibited by scopolamine. The research design was Complete Randomized Design (RAL) – factorial on thirty six mice divided into 4 groups. One control group received only aquabidest (negative control). Three treatment groups received total triterpen 16 mg/kg BW, 32 mg/kg BW orally and piracetam 500 mg/kg BW by intra peritoneally (positive control) for 21 days. Data indicating learning and memory process of all subjects were obtained from one-trial passive avoidance test. Data were analyzed by two way ANOVA and BNT (p<0,05). Result showed that total triterpen 32 mg/kg BW had significantly prolonged the retention time compared to control group indicating improvement in cognitive function (505,03 second vs -18,53 second) (p<0,05) and it was not significantly different to piracetam 500 mg/kg BW group (505,03 second vs 522,48 second) (p>0,05). In conclusion, total triterpen from pegagan (Centella asiatica (L) Urban) improved learning ability and memory of male albino mice (Mus musculus) even though, it was inhibited by scopolamine.